The folklore life among Slovene compatriots in Sweden - Podvinski, Zvone (Two Homelands, 2001)
The author of the contribution, a Slovene clergyman in Sweden, describes on the basis of oral sources and archival materials the activities of Slovene folklore groups in Halmstad, Malmö, Göteborg, and of an infant folklore group in Nybr. In the conclusion the author asks the homeland Slovenia to take better care of its people around the world. Preserving Slovene culture in foreign countries is an important activity within the consolidation of Slovene identity among the emigrants. Slovene folklore groups have their role in the process. In Sweden they were strongly active ten and more years ago while today that part of cultural activity among Slovenes in Sweden completely died away.